Adaptive event‐triggered tracking control for nonlinear networked systems with dynamic quantization and deception attacks - Liu, Xi‐Ming; Chang, Xiao‐Heng (International journal of robust and nonlinear control, 2024)
The problem of adaptive event‐triggered security tracking controller design is studied for interval type‐2 (IT2) Takagi‐Sugeno (T‐S) fuzzy‐approximation‐based nonlinear networked systems with deception attacks, privacy protection, and dynamic quantization in this paper. To reduce the network burden, the adaptive event‐triggered schemes (AETSs) and dynamic quantization are introduced to reduce unnecessary transmission and the number of network packets, respectively. Under the framework of network security, a novel security co‐design scheme with the tracking controller, AETSs, and the quantizers is developed, in which the privacy protection of the reference model and the deception attacks of the controller are taken into consideration simultaneously. Sufficient conditions for the results system to be mean‐square asymptotically stable with a H∞$$ H_{∞ } $$ tracking performance are established. Finally, two practical simulation examples demonstrate the effectiveness and novelty of the proposed design strategy.